Pot losses and associated implications in Barents sea snow crab fishery - Kristine Cerbule; Roger B. Larsen; Astrīda Rijkure (Scientific Reports)
Abstract Snow crab (Chionoecetes opilio) is considered an invasive species in the Barents Sea, with the first observations dating back to 1996. The Norwegian commercial snow crab fishery started in 2012. In this fishery conical baited pots are adopted, similar to fisheries in other areas that target snow crabs. Over the last decade, different management measures have been implemented to ensure sustainability in this relatively new fishery. One central challenge is pot loss during deployment caused by challenging weather and operational conditions. Lost snow crab pots exhibit considerable potential for the continuous capture of crabs, so-called ghost fishing, which has been documented during lost gear retrieval and experimental trials. This study accounted for different snow crab pot loss scenarios and associated economic implications. The results show that given the substantial number of pots on snow crab fishing vessels, even small variations in pot loss rates (pot losses ranging from 0.5 to 3.0%) could result in considerable differences in ghost fishing amounts and the associated environmental and economic effects. The estimated amounts of ghost fishing in this study ranged from 11.5 to nearly 70 tonnes of ghost-fished crabs over a 3-year period, assuming 0.5–3.0% pot loss scenarios, resulting in significant differences in the amount of ghost-fished snow crabs and the value of the ghost fishing catch. These results highlight the importance of incentives and technical measures that can reduce pot losses and the associated ghost fishing time.